IMPLEMENTASI UNCLOS 1982 DALAM PERLINDUNGAN LINGKUNGAN LAUT: STUDI KASUS PENCEMARAN MINYAK DI LAUT BINTAN - Lopo, Dion Reyvaldo Sar (Universitas Labuhanbatu, 2025)
Indonesia as a maritime country with two-thirds of its territory being sea faces major challenges in preserving the marine environment, especially due to shipping and oil exploration activities. This study aims to analyze the implementation of the 1982 United Nations Convention on the Law of the Sea (UNCLOS) in protecting the marine environment in Indonesia through a case study of oil pollution in Bintan waters. The research method used is normative juridical, with an analysis of the provisions of UNCLOS Chapter XII and national regulations, such as the PPLH Law, PP 19/1999, etc. The results of the study shows that Indonesia has ratified the provisions of UNCLOS into national law, but still faces obstacles in law enforcement, coordination between institutions, and supervision in border areas. The repeated cases of oil pollution in Bintan highlight the weak supervision of tanker waste disposal and the need to strengthen the emergency response system. This study recommends increasing international cooperation, harmonizing regulations, and strengthening law enforcement capacity in order to realize the sustainability marine environmental protection in Indonesia. Keywords: Bintan Sea; International Maritime Law; Marine Protection; Oil Pollution.